The Neighborhood Environment Walkability Scale for the Republic of Korea: Reliability and Relationship with Walking - Hyunshik KIM; Younglae CHOI; Jiameng MA; Kuam HYUNG; Masashi MIYASHITA; Sunkyoung LEE (Tehran University of Medical Sciences, 2016)
Background: The aim of the study was to analyze the reliability of the Korean version of the NEWS and to investigate the relationship between walking and environmental factors by gender. Methods: A total of 1407 Korean adults, aged 20-59 yr, participated in the study. Data were collected between Sep 2013 and Oct 2013. To examine the test-retest reliability, 281 of the 1407 participants were asked to answer the same questionnaire (Korean NEWS-A scale) after a 7-d interval. Results: The ICC range of the entire questionnaire was 0.71-0.88. The item on land use mix-diversity had the highest ICC, and that on physical barriers had the lowest. In addition, presents the partial correlation coefficients for walking and the NEWS-A score, adjusted for social demographic variables. Overall, land use mix-diversity (P<0.034) and land use mix-access (P<0.014) showed a positive relationship with walking. Discussion: Examination of the reliability of the Korean NEWS-A scale based on Korean adults who reside in large cities showed that all items had statistically satisfactory reliability. Korean NEWS-A scale may be a useful measure for assessing environmental correlates of walking among population in Korea.   Keywords: Environment, Physical activity, Korean NEWS-A, Reliability